The role of shared ethnicity in facilitating stepwise migration of educated and skilled individuals: The case of Iranian graduate students in Turkey. Issue 2 (1st October 2018) - Sadri, Homa; Chaichian, Mohammad A.
In this article, we examine the status of Iranian graduate students as stepwise global skilled migrants who enrol at Turkish universities, but with the intention of moving to their final destination country in the West. Based on survey data we analyse their migration strategies and career plans at mezzo-level, and conclude that more than 72 per cent of respondents can indeed be classified as stepwise migrants. First, Turkey is a preferred intermediate country particularly for migration of Iranian graduate students of Turkish‐Azeri ethnolinguistic origins. Second, they use social media to communicate with a global social network of friends to facilitate their move to the final destination country. Third, equipped with accumulated 'migrant capital' in Turkey they select a final target country based on its employment prospects, extent of democratic freedoms and the quality of higher education. Finally, while in Turkey, as job seekers they also monitor fluctuations in global demands for skilled workers in their respective disciplines.